Wspieranie działalności innowacyjnej przedsiębiorstw w Polsce - Panenka, Alicja (Supporting the innovation activities of enterprises in Poland, 2006)
Creating the knowledge-based economy in the large part is based on supporting innovations of enterprises. The European Union already in the Lisbon Stategy, that was formed in the year 2000, has focused attention on transforming the EU’s economy in one of the most competitive knowledge-based economy in the world till 2010. Also in 2004 has confirmed it by verifying the progress in realization of the Lisbon Strategy and creating its new version where the main attention was given to obtaining two objectives: baseing growth on knowledge and innovations and creating more better jobs. Polish enterprises are characterized by lower level of innovations in comparison with enterprises from other countries of the EU. Since a short time there are in our country some legal rules that are facilitating the co-operation between firms and R+D sector. Nevertheless, it seems that the legal initiatives that are being undertaken lately could significantly improve this situation. Sectoral Operational Programme - Growth Competitiveness of Enterprises for the period between 2004 and 2006 seems to be a very important initiative that can contribute in increasing the level of innovations of Polish companies and strenghten co operation with R+D sector. The attention is also given to business support institutions which can obtain support for improving their services. Some hope gives also the National Growth Plan for the period between 2007 and 2013, where the issues of supporting innovations of enterprises, co-operation of private sector with research units, investments in innovative venture were placed in horizontal programme, which is one of the five horizontal programme included in the Plan.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (13); 2006; nr 1127, s. 165-177